ANALISIS KESALAHAN BERBAHASA TULIS PADA PROPOSAL KEGIATAN HMJ BAHASA DAN SASTRA INDONESIA UNIMED BERDASARKAN PUEBI - Miyana Dewi E. Sitepu; Yulinda Saragih; Fadhylah Zaini Pardede; Elly Prihasti Wuriyani; Rio Hamonangan Sipahutar; Mesti Herniat Permata Zebua (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to find and categorize errors in the written proposal for the "Language Month Celebration" event on Heroes' Day 2023 compiled by the Indonesian Language and Literature Student Association at Medan State University, in accordance with the General Guidelines for Indonesian Spelling (PUEBI). This study used a qualitative descriptive method with the "Listen and Note" technique (seeing and noting). The data analysis process was carried out in four stages: identification, grouping, explanation, and correction. The findings of this study showed that there were 16 errors detected, consisting of 4 errors in the use of capital letters, 5 spelling errors, 4 errors in the use of punctuation, and 3 errors in writing loan words. Spelling errors were the most common. These findings indicate that the application of PUEBI in official documents created by student organizations needs to be further improved and enhanced Kata Kunci: analisis kesalahan berbahasa, bahasa tulis, proposal kegiatan,PUEBI.